The role of the mucosa in modulation of evoked responses in the spinal cord injured rat bladder. Issue 5 (10th February 2018) - Doyle, Claire; Cristofaro, Vivian; Sack, Bryan S.; Mahmood, Fabliha; Sullivan, Maryrose P.; Adam, Rosalyn M.
Abstract : Aims: Mounting evidence indicates that a variety of factors released from the urothelium or suburothelium can modulate smooth muscle activity. Although the relationship between the mucosa and smooth muscle has been investigated, little is known about the pathophysiologic changes in detrusor‐mucosa interactions in neurogenic bladders. The goal of the study was to determine the impact of the mucosa on evoked responses in spinal cord injured (SCI) bladders. Methods: Urinary bladders were obtained from 6wk SCI rats or age‐matched uninjured controls. Ex vivo isometric tension studies were performed and muscarinic receptor expression was measured in bladder tissue with and without mucosa. Results: The magnitude and area of nerve evoked responses in SCI tissue with mucosa was higher than without mucosa. The duration and decay time of nerve‐evoked responses were longer in SCI than control tissue irrespective of the mucosa. The level of the muscarinic M2 receptor was decreased in the mucosa of SCI bladders. Conclusions: Detrusor‐mucosa interactions are substantially altered in the neurogenic bladder. After spinal cord injury, an excitatory modulation of smooth muscle contraction by the mucosa emerges, and could be targeted via intravesical treatment in the context of neurogenic bladder dysfunction.